Effect of Treating the Black Seed Plan, Nigella sativa L. With Nano-iron Oxide and Vitamin C on Some Physiological Traits and Yield. - Al-Bayaty, Ayyub J.Abdlrahmaan (Universitas Muhammadiyah Sidoarjo, 2025)
In this study we sought to determine the effects of spraying nano-iron oxide and vitamin C on certain physiological traits, yield components, and volatile oil content of black seed plant (Nigella sativa) during the 2023 season, November 5. Concentrations of nano-iron oxide (0, 40, 80, 120 mg L⁻¹) and vitamin C (0, 50, 100 mg L⁻¹) were applied as foliar sprays to plants cultivated in plastic pots using a completely randomized design (CRD) in experiment. Results indicate that the treatment of 120 mg L⁻¹ nano-iron oxide together with 100 mg L⁻¹ vitamin C produced a highly significant improvement on most of the selected traits. The treatment proved better in yield components of plant such as number of capsules per plant (34.50), number of seeds per capsule (48.17), 1000 seed weight (3.99 g) and volatile oil percent (2.09%).